CSR politics of non‐recognition: Justification fallacies marginalising criticism, society, and environment. (29th July 2020) - Norberg, Peter
Abstract: Business is frequently criticized for not taking social and environmental responsibility. Large companies respond with CSR activities and some also with formulating justifications for their actions. This could indicate that business opens up to the criticism. I do, however, not observe such openness in the current study, but how companies use "CSR justifications" to fend off criticism. While companies use justifications as tool for creating legitimacy, I distinguish five justification fallacies. These failures in dealing with criticism cause a marginalisation of criticism, society, and environment. The fallacies found are neglecting criticism, shareholder primacy, organisation‐centricity, conflict avoidance, and progressivism. I contribute to the use of Habermasian ethics in the business ethics literature by showing how CSR justifications could play a part in a rational discourse. The concept justification fallacy, and the five fallacies can provide a framework for analysing corporate rhetoric more generally. Managers have fundamental difficulties in handling ethics and do not reflect on their reasons for working with CSR. They should be more careful when formulating justifications. In our situation of increasing affective polarisation, business needs to be more constructive than merely to marginalise criticism.